Karakteristik Stomata Tempuyung (Sonchus arvensis L.) dan Hubungannya dengan Transpirasi Tanaman di Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang - Izza, Faizatul (Prosiding KPSDA, 2015)
Has conducted research on the characteristics of Sonchus arvensis L. stomata. This study aims to determine the number of stomata with 40x10 magnification, the number of stomata open and closed, the density and type of stomata on the leaf surface above and below the 4, 5, and 6. The method used in this study using the replica method. The results of the study, the number of stomata more found at the bottom of the leaves, as well as tighter density in the area under the surface of the leaf. Type of stomata although in different areas of the plant and there are different types of stomata. Closely related to stomata transpiration activity because most of transpiration or water loss process through stomata.